Typification of the junos names (Iridaceae) published by A.I. Vvedensky - Boltenkov, Eugeny V. (Phytotaxa, 2016)
A total of thirteen names of the juno irises (Iridaceae) were published by the Russian botanist Aleksey Ivanovich Vvedensky (1898–1972), and now some of these names are in need of typification. The holotypes for the names Juno capnoides, J. hippolyti, J. inconspicua, J. nicolai, J. tadshikorum, J. vicaria, and J. zenaidae are here indicated; the lectotypes for the names Iris subdecolorata, Juno leptorrhiza, J. maracandica, J. popovii, and the neotype for J. svetlanae are here designated. Furthermore, the name Juno parvula is here validated. The original material was collected from the Central Asian republics of the former Soviet Union (especially Uzbekistan) and deposited mainly in the Central Herbarium of Uzbekistan (TASH).